Boots and Suits : Historical Cases and Contemporary Lessons in Military Diplomacy - Kosnett, Philip (Book collections on Project MUSE., 2023)
"Boots and Suits, edited by Ambassador Philip S. Kosnett (Ret), discusses aspects of military diplomacy, featuring an edited collection of chapters by ambassadors, scholars, and servicemembers. This diverse set of authors explains military diplomacy through the lens of both the military and the diplomatic corps of countries, including perspectives from the United States, the Netherlands, and Turkey, among others. This volume will examine the aspects of military diplomacy as used by nations and what differentiates this concept from both military confrontation and diplomatic overtures when used as discrete concepts by nation-states rather than employing military diplomacy to advance their strategic goals"--